Bukti Arkeologi Islam Di Barus Berdasarkan Batu Nisan: Klasifikasi Dan Budaya - Maler, S. Wani (2021)
This Master's level Islamic archaeological study involves a site in Barus located on the west coast of North Sumatra, which is facing the east of Nias Island and the Indian Ocean. This study involves five ancient cemetery complexes, which are Mahligai Cemetery, Papan Tinggi Cemetery, Tuan Ambar Cemetery, Tuan Ibrahim Syah Cemetery and Tuan Machdum Cemetery. The main aim of this study is to determine the is to determine the morphology of gravestones, to ascertain the cultural inscriptions and decorative patterns, as well as to find out the historical background of the beginning of Islam in Barus based on gravestones. Hence, literature review, survey and mapping of each gravestones had been conducted in Barus in order to record all pieces of evidence on the morphology, decoration and inscription of the gravestones. The results of this study successfully recorded 670 gravestones that comprise 260 chiselled gravestones, 269 that directly used natural rocks as gravestones, and 141 with damaged gravestones. Analyses in the laboratory towards the 260 chiselled gravestones had determined that they can be categorised based on shape into flat (165), cylindrical (92) and block (3). Classification of the origin of the gravestones based on morphology revealed that 80.0% (208) gravestones in Barus had been carved and designed based on local tradition. The inscription of the earliest date found, which is AD 1350, shows that the early Islamic tradition of the region was more likely developed due to local influences rather than foreign. It was only during the 15th century that foreign influences had started to widely spread based on the discovery of gravestones with Acehnese, Parsin and Indian influences